Genetic polymorphisms within the ETAA1 gene associated with growth traits in Chinese sheep breeds. (30th March 2022) - Wijayanti, Dwi; Erdenee, Sarantsetseg; Akhatayeva, Zhanerke; Li, Haixia; Li, Jie; Cai, Yong; Jiang, Fugui; Xu, Hongwei; Lan, Xianyong
Summary: Ewing tumor ‐ associated antigen 1 ( ETAA1 ) is an important candidate gene for fat deposition in sheep. This study aimed to investigate the indel variations in the ETAA1 gene and their associations with growth traits in the 1619 sheep. The polymorphism information content of this indel ranged from 0.308 to 0.375, with medium genetic diversity (0.25 ≤ polymorphism information content ≤ 0.5). The correlation analysis showed that an 8‐bp insertion within the ETAA1 gene was significantly associated with growth traits in Luxi Blackhead sheep (LXBH), Lanzhou fat‐tailed sheep, Hu sheep, Tong sheep, and Tan sheep ( p < 0.05). Furthermore, the ETAA1 gene was significantly associated with several growth traits ( p < 0.01), such as chest width and paunch girth of LXBH, Tong, and Tan rams. It was significantly related to the body morphometric traits of LXBH, Lanzhou fat‐tailed sheep, Hu, Tong, and Tan ewes. In conclusion, the detected 8‐bp indel within the ETAA1 gene was confirmed in sheep, significantly affecting the growth traits, and might be a potential DNA marker for the selection of high‐quality individuals in marker‐assisted selection for sheep breeding.